Impact of S100A8/A9 expression on prostate cancer progression in vitro and in vivo - Grebhardt, Sina; Müller-Decker, Karin; Bestvater, Felix; Hershfinkel, Michal; Mayer, Doris (Journal of cellular physiology, 2014)
The proinflammatory S100A8/A9 proteins, which are expressed in myeloid cells under physiological conditions, are strongly expressed in human prostate cancer epithelial cells. Their role in the tumor cells and in tumor progression is largely unclear. We established a prostate cancer epithelial cell line (PC-3 TO-A8/A9) expressing S100A8 and S100A9 simultaneously under doxycycline control, to study the role of S100A8/A9 on tumor growth and infiltration of immune cells in subcutaneous xenografts in male NMRI nu/nu mice. Colonization of distant organs was studied after intracardial injection of the tumor cells in male NOD/SCID mice. PC-3 TO-A8/A9 cells grown in vitro and subcutaneous xenografts in mice not treated with doxycycline expressed high levels of S100A8/A9 mRNA and protein, whereas doxycycline treatment suppressed S100A8/A9 expression. S100A8/A9 expression did not significantly alter growth rate and invasion of the subcutaneous tumors into surrounding tissues. However, S100A8/A9 expression caused increased infiltration of immune cells, especially neutrophils. In intracardially injected mice sporadic tumor settlement was observed in muscle and lymph nodes. Colonies of tumor cells and micro-metastases were observed in the lung of 64.3% (9 out of 14) of mice not treated with doxycycline and in 33.3% (5 out of 15) of mice treated with doxycycline. Our data demonstrate for the first time that S100A8/A9 expression in epithelial cancer cells causes enhanced infiltration of immune cells, especially neutrophils, and stimulates settlement of the cancer cells in the lung. J. Cell. Physiol. 229: 661-671, 2014. © 2013 Wiley Periodicals, Inc.
First published: 10 October 2013
Gesehen am 14.01.2021